Factor analysis on the public open space affecting the housing price in Kuala Lumpur, Malaysia - Asmawi, M. Zainora; Abdul Mohit, Mohammad; Hj. Mohd. Noor, Norzailawati; Abdullah, Alias; Paiman, Tuminah (2017)
There is an urgent need for public open spaces within the urban fabric as it provides significant services to the environmental quality of the areas. It is noticeable that many cities in Malaysia have the issue of the loss of public open spaces to give way to other developments particularly housing development. While, about the economic growth of the nation, there is an increasing trend in the housing price in cities. As such, the aim of the research is to study and examine the characteristics of the relationship between public open spaces and residential property value using GIS-Hedonic pricing modelling in Kuala Lumpur, Malaysia. Thus, the objectives which are to study the relationship between public open space and property residential price and to examine the elements of open space which influence the house price. A structured close-ended questionnaire survey with a total of 200 respondents was conducted to obtain the primary data in Taman Melati and Taman Wangsa Siaga, Kuala Lumpur. The results demonstrate that the establishment of the relationship between open space and house price is positive, with the factors of built-up area, an attractive design and provision of a garage are preferable for the buyers. Strategic location and proximity to facilities and infrastructure are the main house attributes in influencing the house price.